NEGOSIASI SOSIAL ATAS KEPEMILIKAN SESAN PASCA PERCERAIAN KARENA PERSELINGKUHAN: STUDI PADA KOMUNITAS ADAT LAMPUNG PEPADUN DI KECAMATAN MARGA TIGA - Rahmanita, Ajeng Gaiska; Asnawi, Habib Shulton; Mukhlisin, Ahmad; Nawawi, M. Anwar (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This study aims to explore the social perception of the Lampung Pepadun indigenous community regarding the ownership of sesan following divorce due to infidelity. Sesan refers to household goods provided by the bride’s family in traditional marriages, serving symbolic, social, and cultural functions. Employing a qualitative approach and case study method in Nabang Baru Village, Marga Tiga District, this research investigates family deliberation dynamics, gender relations, and value shifts in post-divorce sesan distribution. The findings reveal that in infidelity cases, the wife’s family assumes authority over the sesan without formal involvement of customary leaders. Family deliberation becomes the primary mechanism to uphold social justice, with the sesan redirected to the child as a moral responsibility. Pepadun custom in this context shows flexibility it is not rigid, but remains alive through social negotiation. Women emerge as active agents defending rights and family dignity. The study concludes that the indigenous social system is not static but adaptive to the realities of domestic conflict, emphasizing moral legitimacy and community-based justice through deliberative practices. Keywords: Sesan, Pepadun, Divorce, Gender, Social Negotiation